(untitled) (Qualitative Research Journal for Social Studies, 2026)
Iron deficiency anemia (IDA) remains one of the most common nutritional disorders among pregnant women, particularly in low- and middle-income countries. Despite various public health interventions, the burden of IDA continues to affect maternal and neonatal health outcomes in South Asia. The research project aims to assess the nutritional status, dietary patterns, and prevalence of IDA among pregnant women in their first and second trimesters at Hameed Latif Hospital, Lahore. A cross-sectional study was conducted on 132 pregnant women diagnosed with IDA. Data were collected using structured questionnaires covering sociodemographic, anthropometric, and dietary information, along with hemoglobin and serum ferritin levels. The mean age of participants was 27.3 ± 4.8 years. The prevalence of moderate anemia was 58.3%, while severe anemia was found in 18.9% of women. Mean hemoglobin was 9.7 ± 0.9 g/dL, and mean serum ferritin was 11.8 ± 3.4 µg/L. Mean dietary iron intake (13.2 ± 5.1 mg/day) was below the WHO-recommended level (27 mg/day). The findings highlight a high prevalence of IDA among pregnant women in Lahore, underscoring the need for nutrition education, dietary diversification, and improved iron supplementation adherence during antenatal care.